Training on Selecting Environmentally Friendly Packaging with a Green Tourism Concept for MSME Actors in Denai Lama Tourist Village, Deli Serdang - Sitorus, Nova Bernedeta; Indra, Febryola; Maleachi, Sandra (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
The tourism industry serves as a vital mechanism for maintaining environmental sustainability through Green Tourism implementation, particularly regarding eco-friendly packaging adoption. MSMEs in Denai Lama Tourism Village continue to encounter obstacles stemming from limited awareness and insufficient access to information about sustainable practices. A Community Service Program was executed through structured training sessions, employing pre- and post-test methodologies to assess knowledge acquisition. Findings revealed substantial improvements in MSME understanding concerning eco-friendly packaging significance, environmental implications, and economic advantages. The program aims to enhance MSME readiness for implementing sustainable practices, strengthen tourist destination appeal, and create pathways for advanced training in waste management and sustainable product development.